The reaction specificities of the thylakoidal processing peptidase and Escherichia coli leader peptidase are identical. - Halpin, C (1989)
Proteins which are transported across the bacterial plasma membrane, endoplasmic reticulum and thylakoid membrane are usually synthesized as larger precursors containing amino-terminal targeting signals. Removal of the signals is carried out by specific, membrane-bound processing peptidases. In this report we show that the reaction specificities of these three peptidases are essentially identical. Precursors of two higher plant thylakoid lumen proteins are efficiently processed by purified Escherichia coli leader peptidase. Processing of one precursor, that of the 23 kd photosystem II protein, by both the thylakoidal and E. coli enzymes generates the correct mature amino terminus. Similarly, leader (signal) peptides of both eukaryotic and prokaryotic origin are cleaved by partially purified thylakoidal processing peptidase. No evidence of incorrect processing was obtained. Both leader peptidase and thylakoidal peptidase are inhibited by a synthetic leader peptide.